ä½¿ç”¨äº¤é™…æ³•æé«˜å¦ç”Ÿä¸Šé˜…è¯»è¯¾çš„ç§¯æžæ€§ - aisyah, Nur; ., Ina; Khiong, Bun Yan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
æ‘˜è¦ï¼šæœ¬æ–‡çš„ä¸»è¦ç›®çš„æ˜¯äº†è§£äº¤é™…æ³•å¯¹å¦ç”Ÿå¦ä¹ æ±‰è¯é˜…è¯»è¯¾çš„æ•ˆæžœï¼Œæ˜¯å¦æœ‰æ•ˆæé«˜å¦ç”Ÿä¸Šé˜…è¯»è¯¾çš„ç§¯æžæ€§ã€‚ç ”ç©¶å¯¹è±¡æ˜¯ä¸¹å¤§ä¸æ–‡ç³»å¤§ä¸€Bçå¦ç”Ÿï¼Œä¸€å…±æœ‰11åå¦ç”Ÿï¼ˆç”·ç”Ÿ2åï¼›å¥³ç”Ÿ9åï¼‰ã€‚ç ”ç©¶æ–¹æ³•æ˜¯å®žéªŒæ³•ã€‚æ ¹æ®æœ¬æ–‡çš„ æ•™å¦å®žéªŒçš„ç»Ÿè®¡ä¸Žåˆ†æžï¼Œç¬”è€…äº†è§£åˆ°äº¤é™…æ³•æ£æ˜¯é€‚åˆè¿ç”¨äºŽæ±‰è¯é˜…è¯»æ•™å¦ã€‚åœ¨é˜…è¯»æ•™å¦ä¸è¿ç”¨äº¤é™…æ³•ï¼Œä¸ä»…èƒ½æ´»è·ƒè¯¾å ‚æ°”æ°›ï¼Œè€Œä¸”èƒ½æé«˜å¦ç”Ÿå¦ä¹ çš„ ç§¯æžæ€§ã€‚ å…³é”®è¯ï¼šäº¤é™…æ³•ï¼Œæ±‰è¯é˜…è¯»è¯¾ï¼Œç§¯æžæ€§ Abstract :The purpose of this research is to know the effect of communication teaching method for the student to learn mandarin reading lesson, to know that if it can increase the studentsâ€™ activeness in reading lesson.The object of this research is the second semester class B of Mandarin study program of Tanjungpura University Students, with total students were 11 students (2 male; 9 female). The research method is Â practice. Based on the analysis of the teaching learning process in the classroom , The writer gets that result communication teaching method is very appropriate in teaching reading. By using communication teaching method on reading lesson, it is not only able to create a dynamic classroom atmosphere, but also to increase studentsâ€™ activeness in learningã€‚ Key words: communication teaching method, mandarin reading lesson, activeness